5PSQ-030 Use and effectiveness of tigecycline in a private care hospital. (2nd March 2018) - Serrano, D; Fernandez, J; Romera, S; Alonso, P; Corderi, A; Roig, S
Abstract : Background: Tigecycline is a restricted use drug in hospital because of its use in patients with complicated infections and resistant microorganisms. Several cases of tigecycline use were observed in the Emergency Department. Purpose: Evaluation of the usefulness, effectiveness and safety of tigecycline after observing an increase in use in the Emergency Department. Material and methods: Observational and retrospective study carried out in a 300-bed private care hospital. Patients who started tigecycline between February 2013 and February 2017 were selected. Data on usefulness were collected: duration, source of infection, severity, treatment (empirical or directed), adaptation according to local treatment guidelines, isolated microorganisms and resistance profile. Effectiveness was analysed through clinical and microbiological response. Safety was assessed with the appearance of side-effects during treatment. Results: Forty-one patients (70% males) were collected. The mean age was 64-years-old (SD:13.9). The mean duration of treatment was 12 days (SD:17). In 26 (64%) patients the treatment was directed and in 11 (26%) it was empirical. In four (10%) patients the treatment was considered inadequate. The main foci of infection were: 17 (41%) intraabdominal, seven (17%) skin and soft tissue, and four (10%) biliary tract. Sixteen patients (39%) required treatment in the intensive care unit (ICU). The main isolated pathogens were enterobacteriaceae in 16 patients (39%), of whom six had extended-spectrum beta-lactamases and two klebsiella pneumoniae had carbapenemases and enterococus sp (mostly E. faecium ) in 15 patients (37%). Regarding the effectiveness, 25 (61%) clinical responses, six (15%) microbiological responses with pre-discharge culture and 27 (66%) without microbiological results. Side-effects were observed in eight (20%) patients and were mostly abdominal (nausea, epigastralgia) and urticaria. A single patient had to finish treatment for severe rash. Conclusion: Tigecycline is an antibiotic used for intra-abdominal infections and in a high percentage of critically ill patients. Most of the treatments were directed especially for enterobacteria and enterorocus sp . The clinical response was observed in the main of the patients, whereas the microbiological response was detected in a few patients because of the absence of culture at the end of the treatment. The toxicity of the drug was mostly dermal and abdominal, and it was usually well tolerated. Inadequate treatments (10%) were detected in the Emergency Department and these were suspended before 12 hours. The Pharmacy Department and the Microbiology Department established an antibiotics uses' guideline in the Emergency Room. Tigecycline was restricted to internal medicine in hospitalised patients and ICU patients. References and/or Acknowledgements: Acknowledgments to the Internal Medicine Department and the Microbiology Department. No conflict of interest